Java-Based NS2 Network Analyzer - Jabbar, Ayad Mohammed (2011)
The performance of the network may not be as good as the one estimated before the installation. Hence, installing the computer networks in the different peripherals is cost effective when we need to change of the peripherals. Therefore, it is always better to have a simulation of the network rather than the actual establishment. As such, there are many simulators. NS-2 is one of the most popular open source network simulators that widely used in research community, which generates trace file during the simulation experiment. The trace file contains all network events that can be used to calculate network performance. After simulation, the researchers spend much time for analyzing the trace file using traditional scrip tools such as awk or pel to accumulate the result. This project presents Java-Based NS-2 network analyzer (JDNA) as a tool for extracting, analyzing and plotting trace files for the network simulation environment of NS-2. This analyzer enables researcher to analyze and visualize NS-2 trace file quickly and efficiently. It has the ability to visualize more than one trace file simultaneously as well as support all NS-2 trace format. In addition, this project can be a useful guideline to other network researchers or programmers to analyze their networks and to understand how to calculate network performance metrics.